3D hierarchical MnO2 microspheres: a prospective material for high performance supercapacitors and lithium-ion batteries. Issue 8 (6th September 2017) - Khalid, Syed; Cao, Chuanbao; Naveed, Muhammad; Younas, Waqar
Abstract : 3D hierarchical MnO2 microspheres with an ultrathin nanosheet structure and high specific surface area (184.32 m 2 g −1 ) are synthesized by a rapid microwave heating method in just 10 minutes. Abstract : 3D hierarchical MnO2 microspheres with an ultrathin nanosheet structure and high specific surface area (184.32 m 2 g −1 ) are synthesized by a rapid microwave heating method in just 10 minutes. In this work, an ionic electrolyte (EMIMBF4 /DMF) based asymmetric supercapacitor device is successfully prepared by using 3D hierarchical MnO2 microspheres as the cathode and activated carbon as the anode material. The (EMIMBF4 /DMF) electrolyte enables a significant enhancement in the potential windows of individual electrode materials and the asymmetric device which results in much improved electrochemical performance. The asymmetric device operates successfully within a potential window of 3.0 V and exhibits an outstanding energy density of 105 W h kg −1 at a power density of 1494 W kg −1 with good cycling life stability (20% loss after 6000 cycles) at a much higher current density of 6 A g −1 . Moreover, 3D hierarchical MnO2 microspheres also exhibit an outstanding Li ion storage performance with a discharge capacity of 715 mA h g −1 even after 200 cycles at a current density of 300 mA g −1 . The discharge capacity retention (78% @ the 2nd cycle) after 200 cycles at 300 mA g −1 is the highest amongst those of all the reported anode materials based on MnO2 . High specific capacities and outstanding cyclability further indicate their strong potential as an anode material for lithium-ion batteries. The promising energy storage applications can be ascribed to the high specific surface area, mesoporous structure and ultrathin nanosheet building blocks of MnO2 microspheres.